Multi-Agent based E-Learning System - Do, Van Nhon; Nguyen, Tran Minh Khue (Journal of Technical Education Science, 2009)
The aim of this paper is to construct a model of the E-Learning system based on Multi-Agent technology. The work includes building component parts of the model along with principles and working processes of them, managing Agents and their communication, providing an environment and mechanisms to design and query the distributed knowledge base. We applied our model in the field of plane geometry.